2018
DOI: 10.1016/j.psychsport.2017.11.010
|View full text |Cite
|
Sign up to set email alerts
|

A needs-supportive intervention to help PE teachers enhance students' prosocial behavior and diminish antisocial behavior

Abstract: Objectives: Grounded in self-determination theory, we implemented an autonomy-supportive intervention program (ASIP) to help physical education (PE) teachers become more autonomy-supportive and less controlling toward their students. We tested whether such changes in teachers' classroom motivating styles could promote students' prosocial behaviors and diminish their antisocial behaviors. Design:We used an experimental research design to manipulate teachers' motivating style and a three-wave longitudinal design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
133
2
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(153 citation statements)
references
References 57 publications
8
133
2
10
Order By: Relevance
“…Specifically, an autonomy-supportive coaching climate was inversely associated with antisocial behaviour toward both teammates and opponents (Hodge & Lonsdale, 2011), while an autonomy-supportive teammate environment negatively predicted antisocial teammate (but not opponent) behaviour (Hodge & Gucciardi, 2015). Finally, in the Autonomy-Supportive Intervention Program implemented with PE teachers (Cheon et al, 2018), students of teachers who took part in the programme reported a decrease in their antisocial behaviour over time; these decreases were attributed to declines in psychological need frustration.…”
Section: Negative Predictors Of Antisocial Behaviourmentioning
confidence: 94%
See 2 more Smart Citations
“…Specifically, an autonomy-supportive coaching climate was inversely associated with antisocial behaviour toward both teammates and opponents (Hodge & Lonsdale, 2011), while an autonomy-supportive teammate environment negatively predicted antisocial teammate (but not opponent) behaviour (Hodge & Gucciardi, 2015). Finally, in the Autonomy-Supportive Intervention Program implemented with PE teachers (Cheon et al, 2018), students of teachers who took part in the programme reported a decrease in their antisocial behaviour over time; these decreases were attributed to declines in psychological need frustration.…”
Section: Negative Predictors Of Antisocial Behaviourmentioning
confidence: 94%
“…In an important intervention study, Cheon, Reeve, and Ntoumanis (2018) implemented an Autonomy-Supportive Intervention Program (ASIP) to help physical education (PE) teachers become more autonomy-supportive and less controlling toward their students and examined whether changes in teaching styles influence students' behaviours during PE. Teachers who took part in the programme increased their autonomy support, and their students experienced greater need satisfaction and engaged in more prosocial behaviours.…”
Section: Prosocial Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have shown a positive relationship between the satisfaction of the BPN and self-determined motivation [13,[22][23][24], as well as between more self-determined motivation and autotelic experience [25][26][27]. Similarly, it has been shown that a climate of support for autonomy is beneficial for students, as it increases their perception of autonomy [28,29]; is related to the satisfaction of the BPN [30][31][32]; produces benefits in motivation and well-being [33]; and increases enjoyment in PE classes [34,35] and the development of life skills [36], thus favouring self-determined motivation and the intention to continue carrying out physical activity [18].…”
Section: Introductionmentioning
confidence: 99%
“…En referencia a estos hechos, la Unidad Educativa "Alto Barinas Norte" ubicada en la ciudad de Barinas, parroquia Alto Barinas, municipio Barinas del estado Barinas, Venezuela, se observó una situación similar vinculada con este tipo de trastorno a nivel individual y grupal en los jóvenes estudiante de educación secundaria. Tal es el caso, Ornelas et al, (2012) ;Cheon, et al, (2018) manifiestan la presencia de agresividad entre los mismos estudiantes involucran a miembros de otros niveles de la institución, poniéndose de manifiesto amenazas, agresiones físicas y el incumplimiento a las normas de convivencia escolar, considerando las definiciones dadas de trastorno disocial, tales expresiones conductuales fueron asumidas como síntomas o probables manifestaciones de este tipo. En tal sentido, la acción docente Bradfield et al, (2015), se refiere a la enseñanza apoyada en el aprendizaje acción.…”
Section: Introductionunclassified